2021
DOI: 10.1073/pnas.2101634118
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones regulate the formation and environmental plasticity of white bars in clownfishes

Abstract: Determining how plasticity of developmental traits responds to environmental conditions is a challenge that must combine evolutionary sciences, ecology, and developmental biology. During metamorphosis, fish alter their morphology and color pattern according to environmental cues. We observed that juvenile clownfish (Amphiprion percula) modulate the developmental timing of their adult white bar formation during metamorphosis depending on the sea anemone species in which they are recruited. We observed an earlie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 54 publications
2
41
0
Order By: Relevance
“…Previous studies in Kimbe Bay (Salles et al 2016) had found that juveniles that settled on H. magni ca grew faster than those on S. gigantea which is slightly different to what we found in our study; our results found sub-adult and adult individuals growing faster on S. gigantea. Juveniles that recruited to S. gigantea had acquired their white bars faster compared to those who recruited to H. magni ca (Salis et al 2021). This could be due to their environment since most S. gigantea individuals were in a sheltered shallow habitat close to shore, compared to H. magni ca, which were further offshore and tended to be in slightly deeper water (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies in Kimbe Bay (Salles et al 2016) had found that juveniles that settled on H. magni ca grew faster than those on S. gigantea which is slightly different to what we found in our study; our results found sub-adult and adult individuals growing faster on S. gigantea. Juveniles that recruited to S. gigantea had acquired their white bars faster compared to those who recruited to H. magni ca (Salis et al 2021). This could be due to their environment since most S. gigantea individuals were in a sheltered shallow habitat close to shore, compared to H. magni ca, which were further offshore and tended to be in slightly deeper water (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies found that, on average, females were 10% larger in H. magni ca compared to those living on S. gigantea, and juveniles that settled on H. magni ca had a faster growth rate based on otolith increments (Salles et al 2016). A recent study (Salis et al 2021) concluded that juvenile A. percula delay the development of their white bars during metamorphosis depending on the anemone species they are hosted by. Additionally, anemone surface area has a signi cant impact on social structure with larger anemones hosting larger social groups and individuals (Chausson et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…The expression level of trh is relatively stable and tshβ expression levels rise from the onset of metamorphosis (stage 4) and stabilize until stage 7. In the thyroid gland, duox have been shown to be critical for TH production and is associated with high TH levels in clownfish (Salis et al, 2021). Interestingly, we observed that its expression levels strongly rise during metamorphosis, starting at stage 5.…”
Section: Resultsmentioning
confidence: 99%
“…Beside the striking larval metamorphosis in eels and flatfishes, studies also report developmental changes controlled by TH during larval to juvenile transition in various teleosts such as grouper Epinephelus coioides (de Jesus et al, 1998), seabream (Campinho et al, 2010), gobiid Sicyopterus lagocephalus (Taillebois et al, 2011), or clownfish Amphiprion percula (Salis et al, 2021). Our review will focus on the well-known pleuronectiform/flatfish metamorphosis.…”
Section: Larval Metamorphosis In Teleosts: the Example Of Flatfishmentioning
confidence: 99%